Krav maga and chicken soup: symbolic Jewish identities within and beyond the Jewish school. Issue 6 (18th August 2019) - Samson, Maxim G. M.
ABSTRACT: Faith schools may play an important role in reproducing ethnoreligious identities, yet research into Jewish schools has tended to overlook students' personalised conceptualisations of faith. Instead, it has regularly utilised restrictive 'indicators' of ethnoreligious practice in order to gauge these institutions' effectiveness in 'strengthening' Jewish identity and thus mitigating assimilation. In response, this article explores the ways in which students at a pluralist Jewish school negotiated and (re)shaped their Jewishness, and thus lived their identities in personally meaningful ways. Students articulated 'symbolic' forms of Jewishness, rooted in inclusive and often stereotypical cultural symbols rather than regular religious practice, and personalised their identities through the school's amenability to diverse manifestations of faith. Consequently, the research illustrates the value of including young people's perspectives of faith and faith schooling, with implications for understandings of ethnoreligious identity and practice in spaces beyond traditional religious sites such as places of worship.